Food Insecurity and Substance Use Among Young Adult College Students in the United States. Issue 2 (30th March 2023) - Oh, Hans; Smith, Lee; Jacob, Louis; Du, Jinyu; Shin, Jae Il; Zhou, Sasha; Koyanagi, Ai
Abstract : Background: Food insecurity is prevalent among college students in the United States and has been associated with substance use. We sought to provide updated prevalence estimates and associations between food insecurity and a broad range of substances during the SARS-CoV-2 pandemic. Methods: Using cross-sectional data from the Health Minds Study (N = 94, 722; September 2020–June 2021), we used multivariable logistic regression to examine associations between food insecurity and several substances, adjusting for age, gender, race/ethnicity, hours worked, and residence. We then added a block of adjustments consisting of mental health factors (depression, anxiety, loneliness, financial stress). Results: Food insecurity was associated with significantly greater odds of having used most individual substances, including greater odds of binge drinking (adjusted odds ratio [aOR], 1.21; 95% confidence interval [CI], 1.13–1.30), cigarette use (aOR, 1.91; 95% CI, 1.73–2.10), vaping (aOR, 1.74; 95% CI, 1.62–1.87), and a range of illicit or prescription drugs (using any illicit/prescription drug; aOR, 1.43; 95% CI, 1.32–1.55) These associations attenuated and many lost significance after adjusting for mental health factors. Conclusions: This study found evidence to suggest that food insecurity is related to substance use in a large sample of young adult college students in the United States, calling for targeted interventions.